Evaluasi Teknologi Sistem Informasi pada Bank Perkreditan Rakyat (BPR) dengan Metode Teknometrik - Mast Rasyid; R Rohmat S; Zaenal Mutaqien (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2012)
Information Technology (IT) is supporting factor in applying of information system representing an organizational solution and management to solve problems of management. These days adjustment of technology of information have clear away various area, including banking area. Special regarding small scale banking area like Bank Perkreditan Rakyat (BPR), adjustment of technology information just conducted at last some years. Unhappily the applying does not follow with evaluation to know technological contribution at their business. By using model of tachometric developed by Asian United Nation-Economic Social Commission for and Pacific(UN-ESCAP), hence can be calculated by technological contribution pursuant to four technological component that is: teknoware, humanware, infoware and orgaware. Trouble-Shooting phase start from phase identify especial item of coherent technological component at information technology of BPR, continued with compilation of assessment criterion and procedure to technological item, and identify relevant responder. Implementation tachometric model on this phase. After process identify, data collecting through admission filling three kinds of questioner, that is: questioner degree of sophistication, questioner assessment of recent sophisticated storey/State of the Art (SOA), and matrix questioner comparison form a pair. Third of the questioner compiled and filled by using justification all relevant responder. From this research is known that approach of model of tachometric represent approach which is practical and can find weakness and strength at technological component of information technology facility wearied by BPR Sukabumi HQ. Value Contribution of each technological component is 0,707 for teknoware, 0,662 for humanware, 0,563 for infoware and 0,512 for orgaware. With the data obtained by result of technological contribution coefficient (TCC) equal to 0,607 showing information technology payload storey of BPR on course goodness. Nevertheless, technological component infoware and orgaware reside in below of TCC. Therefore, the components become furthermore repair priority.